Redesigning special education systems through collaborative problem solving : a guidebook for school leaders - Brenner, Michelle (Special educator); Miller, Kelly (Autism consultant) (New York : Routledge, 2024)
"Special education is facing a period of increasing conflict, which is leading to untenable jobs and an exodus from the field. This important and innovative book offers a framework that can begin to resolve many of the consequential challenges special educators, schools, and students are dealing with. Through a framing of effective leadership built through authentic collaboration, this book outlines how we might stop viewing the issues in special education as insurmountable problems, and instead see them as informative starting points from which to communicate, brainstorm, and organize operative partnerships to find solutions, change practices, and create better outcomes at the level of entire districts as well as individual schools. Redesigning Special Education Systems Through Collaborative Problem Solving is key reading for school and district leaders and administrators, special education teachers, and preservice teachers interested in becoming more productively engaged in creating solutions and making changes in the field of special education"--
Introduction: Why do we need to redesign special education? -- The Power is in the Process -- Six Not-So-Easy Steps for Collaborative Change -- Leveraging Unexpected Partnerships -- Modeling Collaboration: A parallel adult learning process -- Empowering Others -- Strength of Students -- Attracting and Retaining Quality Staff -- Designing Your Innovation.
Keywords: Special education -- Research; EDUCATION / General